Role of ideology and the media in promoting familiarity and trust in political decisions: the case of Argentina's 2019 elections - Emilio Recart Zapata; Emilio Recart Zapata; Tomas Alves Salgueiro; Pablo Nicolas Fernández Larrosa; Pablo Nicolas Fernández Larrosa (Frontiers in Social Psychology)
IntroductionToday's democratic systems are at a crossroads in the face of the rising “new right wing”, a reactive form of political polarization. Although much research has studied the political polarization phenomenon, most focus on the United States and Europe. Previously, we have shown how repeating information or positively associating with content can cognitively induce certain political candidates' election.MethodsWe assess whether familiarity and trust can be voting predictors using the 2019 Argentinean elections as a case study. Previously, we generated two databases from surveys conducted during the 2019 Argentinean presidential election (PASO [Spanish acronym] election: 2,255 participants; general election: 1,418 participants). A logistic regression model was used to predict the probability of choosing a given candidate using the familiarity with and trust in each candidate or consumed media outlets as predictor variables (features). We also evaluate voting communities in a cluster analysis associated with ideological self-perception or media consumption.Results and discussionOur results show that both familiarity and trust, social variables of political interest to manipulate, are key predictors of candidate choice. We find key links between these factors and ideology, media consumption, and candidate choice. We discuss our results in light of the effects of the two-party system, ideology, the role of the media, and their cognitive effects in favoring political polarization. These mechanisms' persistence only serves to erode people's freedoms, damaging relations between different groups and the democratic system in general.